STRATEGI PENINGKATAN DAYA SAING PRODUK LOKAL MELALUI PELATIHAN INOVASI DAN PEMBUKUAN DIGITAL BAGI UMKM YY CAKE DAN BAKERY DI KOTA BIMA - Rosa Yuliati; Sri Astuti; Sabrina Sabrina; Imannurwahyudi Imannurwahyudi; Edy Suptratman; Muhammad Faisal (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to improve the competitiveness of local products through product innovation training and digital bookkeeping at YY Cake and Bakery MSMEs in Bima City. YY Cake and Bakery MSMEs are businesses in the food and bakery sector that have the potential to grow, but still face obstacles in the form of limited product innovation and the suboptimal implementation of digital bookkeeping in business financial management, making it difficult for business actors to develop competitive products and carry out systematic financial records. The methods used in this activity include observation, interviews, socialization, training, and mentoring, where observations and interviews are conducted to identify the needs and problems of MSMEs, innovation training is focused on developing more attractive product variations according to consumer needs, and digital bookkeeping training aims to improve the ability to record financial transactions effectively, efficiently, and structured based on digital technology. The results of the activity show that MSMEs have gained a better understanding of the importance of product innovation and digital financial management, are able to develop innovative ideas to improve product quality, and have begun implementing a digital bookkeeping system in their daily business activities, which is expected to increase the competitiveness of local products, strengthen business management, and support the sustainability of MSMEs YY Cake and Bakery in Bima City.